2019
DOI: 10.3390/cancers11040437
|View full text |Cite
|
Sign up to set email alerts
|

Butoxy Mansonone G Inhibits STAT3 and Akt Signaling Pathways in Non-Small Cell Lung Cancers: Combined Experimental and Theoretical Investigations

Abstract: Epidermal growth factor receptor (EGFR) is the key molecular target for non-small cell lung cancer (NSCLC) due to its major contribution to complex signaling cascades modulating the survival of cancer cells. Targeting EGFR-mediated signaling pathways has been proved as a potential strategy for NSCLC treatment. In the present study, mansonone G (MG), a naturally occurring quinone-containing compound, and its semi-synthetic ether derivatives were subjected to investigate the anticancer effects on human NSCLC cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 85 publications
5
14
0
Order By: Relevance
“…In addition, coimmunoprecipitation assay indicated that genipin inhibited STAT-1:STAT-3 heterodimerization and STAT-3: STAT-3 homodimerization. In previous research, Mahalapbutr et al found that the SH2 domain was critical for EGFR and STAT-3 interaction and subsequent STAT-3: STAT-3 homodimerization [39]. In our study, it was revealed that genipin could suppress EGFR-STAT-3 interaction and further inhibit STAT-3 dimerization.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, coimmunoprecipitation assay indicated that genipin inhibited STAT-1:STAT-3 heterodimerization and STAT-3: STAT-3 homodimerization. In previous research, Mahalapbutr et al found that the SH2 domain was critical for EGFR and STAT-3 interaction and subsequent STAT-3: STAT-3 homodimerization [39]. In our study, it was revealed that genipin could suppress EGFR-STAT-3 interaction and further inhibit STAT-3 dimerization.…”
Section: Discussionsupporting
confidence: 59%
“…In previous research, Mahalapbutr, P et. al found that SH2 domain was critical for EGFR and STAT-3 interaction and subsequent STAT-3:STAT-3 homodimerization [34]. In our study, we revealed that genipin could suppress EGFR-STAT-3 interaction and further inhibit STAT-3 dimerization.…”
Section: Discussionsupporting
confidence: 59%
“…Many lines of evidence have shown that MG exhibits a potent anticarcinogenic effect on various types of malignancies, e.g., ovarian (A278, IC 50 of 10.2 μM), colorectal (HCT116, IC 50 of 63.4 µM), liver (HepG2, IC 50 of 36.3 µM and Huh-7, IC 50 of 25.9 µM), breast (MCF-7, IC 50 of 23.0 µM), and cervical (HeLa, IC 50 of 18.8 µM) cancer cell lines [5,12,13], and it has been documented to significantly inhibit the activity of P-glycoprotein efflux pump [5]. Recently, the butoxy MG has shown to potentially induce cell apoptosis in human lung cancer cell lines A549 and H1975 by inhibiting STAT3 and Akt signaling pathways [14]. Even though MG could serve as a promising anticancer agent, its poor water solubility (1.7 mg/L at 30 °C) leads to a limited use for pharmaceutical and medicinal applications.…”
Section: Introductionmentioning
confidence: 99%